Breastfeeding and Oral Health: Evidence and Methodological Challenges. (March 2018) - Peres, K.G.; Chaffee, B.W.; Feldens, C.A.; Flores-Mir, C.; Moynihan, P.; Rugg-Gunn, A.
Breastfeeding is a powerful health-promoting behavior. A 2016 Lancet global collaboration to review the health implications of breastfeeding was among the first to consider oral health outcomes. While a role was suggested for breastfeeding in preventing malocclusion, caries was the only included disease condition unfavorably associated with breastfeeding. The present critical review examines the evidence connecting breastfeeding practices to these outcomes and discusses the methodological challenges inherent in reaching causal conclusions. Published systematic reviews show some evidence of a protective effect of breastfeeding against primary dentition malocclusion but no supportive evidence for mixed dentition and permanent dentition malocclusions. Regarding caries, well-conducted studies report a benefit with breastfeeding up to 12 mo but a positive association between caries and breastfeeding of longer duration, at times that vary between 12 and 24 mo, as well as nocturnal feeding. Future studies would be methodologically stronger if focused on specific malocclusion traits that are plausibly associated with sucking movements rather than using general malocclusion indices. Studies should use detailed and consistent terminology for breastfeeding definition, including frequency, intensity, and timing. Analytical studies should be carried out to distinguish between confounders (e.g., prematurity) and mediators (e.g., use of pacifier). Regarding a link to caries, standard terminology for exposures (e.g., nocturnal feeding) is recommended. Statistical analyses must account for known confounding factors (e.g., socioeconomic conditions) but avoid inappropriate adjustment for variables on a causal path between exposure and outcome or for variables not associated with breastfeeding (e.g., tooth brushing), as can be guided using tools such as direct acyclic graphs. For dental practice, the potential caries risk of long-duration breastfeeding should be part of individual patient counseling that incorporates patient values and circumstances. Given the unquestioned overall health benefits of breastfeeding, the dental community should support World Health Organization guidelines that encourage and promote breastfeeding.